PENGATURAN DAN PENEGAKAN HUKUM PEMBOIKOTAN DALAM ANTITRUST LAW AMERIKA SERIKAT - Anisah, Siti (Jurnal Media Hukum, 2015)
Boycott is one of violations in the competition law that eliminating the freedom of parties to enter the market. The aim of it no other than lessened fair competition. Theoretically, the issue related boycott discuss about the approach utilised by the authority to investigate and enforce boycott and its meaning: whether boycott is vertical or horizontal, or both; and what are the criteria of the violations? Given so few references on boycott, this paper attempts to reveal the regulation and the enforcement of it in the United States. It is aimed as reference to regulate and/or to settle the competition law cases of boycott in Indonesia in the future day. The United States does not specifically state boycott in the Antitrust Law. The United States includes boycott as concerted to deal and refuse to deal as ruled in the Section 1 of Sherman Act.